ICT IN ENGLISH LANGUAGE TEACHING AND LEARNING - Rashidova Nodira Habibullayevna (American Journals Publishing, 2023)
This article defines that using of information and Communication technologies in english language ateaching and learning. Moreover, there are shown the result of using these technologies.
Keywords: Information and communication technologies, mobile learning, integrated language learning, rural schools.